Surjan Jogja Motif in Modern Visual Communication: A Design Thinking Approach - Priyadi, Agus; Slamet, Ayyub Hamdanu Budi Nurmana Mulyana (University of Science and Computer Technology, 2024)
Traditional culture is a vital part of a community's identity, yet in the era of globalization, cultural elements are often threatened by modernization, which can blur local identities. This study explores the application of the Design Thinking method in integrating the Surjan Jogja motif into visual communication design, focusing on how the design can preserve cultural meaning while remaining relevant in contemporary times. The research employed a qualitative approach, utilizing the five stages of Design Thinking: empathy, problem definition, ideation, prototyping, and testing. Data were collected through in-depth interviews with 15 respondents, including designers, batik artisans, and cultural figures, as well as direct observations of the creative process. The results show that 80% of respondents appreciated designs that integrated the Surjan motif, with many stating that the design offered deeper meaning compared to products without cultural context. The study found that the application of Design Thinking produced innovative visual solutions and strengthened local cultural identity amidst globalization. The conclusion of this study emphasizes the importance of integrating traditional elements in visual communication design to preserve local culture. The practical implications of this research are significant, as it provides a framework for the development of culture-based design and opens opportunities for further research on the application of this method in other cultural contexts, thereby offering a practical guide for designers and cultural researchers interested in preserving local culture through design.